Molar heat capacity and thermal conductivity of single crystals of ZnMgSe substitution solid solution - Kapustnik, A.K.; Zagoruiko, Yu.A.; Kovalenko, N.O. (Functional Materials, 2012)
Determined for the first time are the temperature dependences of thermal conductivity coefficient and molar heat capacity of single crystals of the substitution solid solution Zn₁₋ₓMgₓSe in 25-300°C temperature range. The obtained data are compared with those for control samples of ZnSe single crystal and polycrystalline ZnSe-CVD. The dependence of the density of single crystals of the substitution solid solution Zn₁₋ₓMgₓSe on the concentration of magnesium was found for the first time.